(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This research aims to shed light on the transformation of Maharashtra into India’s economicpowerhouse in the decades following India’s independence. The state’s social problems were only recentlyrecognized, despite the state’s flourishing economy. There has always been a disparity between the sexes,but the patriarchal norms ingrained in the culture have only contributed to exacerbate the problem. Thecontributions of women to the family, the workplace, and society as a whole are little when all the facts areexamined. This necessitated studies into the results of various national and state-level initiatives aimedat fostering better gender equality and relations in spheres such as sex inequality, dowry, women’sproperty rights, domestic violence, family structure, fertility patterns, girl child birth order, infant care,healthy eating, and naming ceremonies. Women’s empowerment will be studied in terms of factors liketheir ability to move freely and financially, their ability to make decisions (both big and small), theabsence of male family influence in significant matters, their access to information about political andlegal issues, and their participation in political campaigns and protests. In this analysis, we look at howthe Short Message Service (SMS) program has affected the health and social consciousness of ruralwomen, as well as their ability to adapt to new gender norms and advance in their communities. It wasthe researcher’s intention to look into the emancipatory effects of SMS in order to learn more about it(SMS). In order to fully grasp the empowerment process, it was crucial to travel to the villages andobserve the events that rural women organize under Sakshar Mahila Samooh, such as rallies, awarenesscamps in the village, organizational activities like monthly meetings, account keeping, role distribution,etc.